Analisis Potensi Pasar Dan Persaingan Wall Decoration Berbahan Metal di Marketplace dengan Metode Roda Deming - Desmarita Leni; Helga Yermadona; Haris Haris; Adriansyah Adriansyah; Ruzita Sumiati (Jurnal Teknik Industri Terintegrasi (JUTIN), 2022)
This research aims to determine the market potential and business opportunities for wall decorations made of metal with CNC laser in the industry by determining the market size, evaluating competition, determining product trends, and identifying business opportunities. The quality management method of Deming's Wheel or PDCA (Plan-Do-Check-Act) is used to analyze the market potential and competition of metal wall decoration products in various marketplaces. The research results show that Shopee is the e-commerce platform that sells the most metal wall decorations in Indonesia. The sales of metal wall decorations on Shopee reached 17,830 units, followed by Lazada with 2,794 units and Tokopedia with 789 units. The most popular motif or design among consumers is the leaf motif, with a total sales of 14,600 units on Shopee. The average monthly sales on Shopee are quite high, where store A is able to sell 160 units of wall decoration. The factors that influence high sales are quick chat replies, high ratings, positive testimonials from customers, and having their own online store website. Having their own online store provides advantages for store owners, such as advertising.